VD_FINDINFO Jug / 2014 / 86 vom 5. September 2014 - VD Tribunal cantonal (2014)
CONTRAT D'ASSURANCE, LOI FÉDÉRALE SUR LE CONTRAT D'ASSURANCE, VIOLATION DE L'OBLIGATION D'ANNONCER | 102 LCA, 4 LCA, 6 LCA